2018
DOI: 10.1111/jace.15712
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic modeling of thermo‐mechanical properties of cubic SiC

Abstract: SiC is an important multifunctional material with application in electronics and as a structural material. Many investigations of SiC have been done using both classical molecular dynamics and first principles methods. However, they are of limited scope and, in particular, SiC properties at finite temperatures have not been adequately evaluated. The good mechanical, thermal, and chemical properties of SiC such as high stiffness, high hardness, high mechanical strength at high temperature, and high thermal cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…and Szpunar et al . are in good agreement, , which are the basis for the following Monte Carlo simulation of the interfacial heat transfer of the CVI-SiC-welded BN–BN interfaces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…and Szpunar et al . are in good agreement, , which are the basis for the following Monte Carlo simulation of the interfacial heat transfer of the CVI-SiC-welded BN–BN interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…All first-principles calculations were performed in the QUANTUM ESPRESSO software based on an h-BN supercell ( a = b = 2.478 Å, c = 6.425 Å 2 , 5 × 5 × 2) and a β -SiC ( i . e ., CVI-SiC) supercell ( a = b = c = 4.357 Å, 3 × 3 × 3), whose k -point samplings were set to the gamma-centered mesh of 2 × 2 × 1 and 1 × 1 × 1, respectively. The harmonic interatomic force constants (IFCs) and phonon properties were obtained using the phonopy package through the density functional perturbation theory (DFPT) method .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Vashishta potential shows agreement with experimental results, except for C 44 for 3C-SiC [ 27 ]. In the field of thermal properties, most studies have focused on the thermal conductivity of 3C-SiC [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] and 4H-SiC [ 35 ]. The research revealed that compared with T89 potential, the thermal conductivity predictions by GW potential closely match the experimental results [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon carbide (SiC) has shown great potential in high-power devices because of its outstanding properties, such as high thermal conductivity, wide band gap, and high electric breakdown field. [1][2][3][4][5] The polytypes of SiC that are most widely employed in micro-and nanoelectronics include 3C-SiC, 4H-SiC, and 6H-SiC, of which the cubic crystallization of SiC is unique to 3C-SiC. 6 With the increasing miniaturization and integration of electronic devices, heat dissipation is now an essential issue restricting their development.…”
mentioning
confidence: 99%